Generic sustained release tablets of trimetazidine hydrochloride: Preparation and in vitro-in vivo correlation studies - Longmei Wang; Ruihua Feng; Jinhua Gao; Yanwei Xi; Guihua Huang (Elsevier, 2016)
The aim of the current work was to develop generic sustained-release tablets containing 35 mg trimetazidine dihydrochloride and to establish an in vitro-in vivo correlation that could predict the bioavailability. The marketed sustained release tablet (Vastarel MR) used as reference, a sustained-release matrix tablet was prepared using hydroxypropyl methylcellulose (HPMC) as matrix by wet granulation and the in vitro dissolution profiles of the self-made tablets were determined in four different dissolution media (0.1 M HCl, pH 4.5 PBS, pH 6.8 PBS and water). A higher similarity between prepared tablets and Vastarel MR was established, with similarity factor (f2) ranging from 60 to 75 in the four media. The in vivo pharmacokinetics was studied in six healthy beagles. Compared with Vastarel MR, the Cmax of self-made tablets was slightly decreased, while the Tmax and MRT0-t were slightly prolonged, but with no significant difference (P > 0.05). The average of relative bioavailability (F) was 102.52% based on AUC0-t. For log-transformed AUC0-t and Cmax, the upper confidence limit on the appropriate criterion is <0, indicating these two formulations were population bioequivalent. The in vivo-in vitro correlation coefficient obtained from point-to-point analysis of self-made tablets was 0.9720. In conclusion, the prepared tablets were bioequivalent to the marketed tablets, according to both the in vitro release rate and extent of absorption, and a good in vivo-in vitro correlation was established for the self-made tablets that indicated in vitro dissolution tests could be used as a surrogate for bioavailability studies.